Analisis Isu Islamophobia Di Jerman: Studi Kasus Muhammadiyah Sebagai Organisasi Gerakan Islam Modernis Indonesia - Agustari Agustari (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2023)
The case of Islamophobia is one of the cases that is often reported in the German media, which is closely related to the failure of multiculturalism politics which has an impact on the emergence of a negative stigma against Islam. Being a Western country with the largest Muslim population in Europe with a total of approximately 5.3 to 5.6 million people, based on data from the Federal Office for Migration and Refugees (BAMF) in 2021, the German government's policy towards Muslim immigrants is very exclusive and limited. Despite the many negative stigmas, Islam has been transformed into one of the major entities whose existence is considered. Muhammadiyah is one of the Islamic organizations in Indonesia that has diasporaized the "Modernist Islam" missionary movement in Germany. Through the modernist Islamic diaspora, Muhammadiyah seeks to explore the issue of Islamophobia by developing a da'wah movement through real programs to raise the positive image of Islam in German society. The method used in this research is a descriptive qualitative approach, which involves conducting a literature review, where all the data used in this study uses secondary data, which includes books, theses, theses, articles, journals, and various news related to this research. The results of this study illustrate that the modernist Muhammadiyah Islamic diaspora in Germany has had quite a positive impact in efforts to minimize the negative stigma of Islamophobia in Germany.